Promoting transparency and reproducibility in enhanced molecular simulations - Bonomi, M.; Bussi, G.; Camilloni, C.; Tribello, G.A.; Banáš, P.; Barducci, A.; Bernetti, M.; Bolhuis, P.G.; Bottaro, S.; Branduardi, D.; Capelli, R.; Carloni, P.; et al. (NATURE PUBLISHING GROUP, 2019)
© 2019, Springer Nature America, Inc. The PLUMED consortium unifies developers and contributors to PLUMED, an open-source library for enhanced-sampling, free-energy calculations and the analysis of molecular dynamics simulations. Here, we outline our efforts to promote transparency and reproducibility by disseminating protocols for enhanced-sampling molecular simulations.